2019
DOI: 10.3892/or.2019.7221
|View full text |Cite
|
Sign up to set email alerts
|

DEPDC1 drives hepatocellular carcinoma cell proliferation, invasion and angiogenesis by regulating the CCL20/CCR6 signaling pathway

Abstract: DEP domain containing 1 (DEPDC1) functions as an oncogene in hepatocellular carcinoma (HCC). However, the underlying mechanism of DEPDC1 remains largely unknown. The present study revealed that DEPDC1 knockdown inhibited HCC cell proliferation, colony formation and invasion in vitro and suppressed the growth of HCC xenografts in vivo. Furthermore, DEPDC1 overexpression promoted HCC cell proliferation, colony formation and invasion. DNA microarray, reverse transcription-quantitative-PCR and western blotting res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…no. C0078S; Beyotime Institute of Biotechnology), according to the manufacturer's protocol ( 29 ). Positive cells were observed under an Olympus IX71 fluorescent microscope (Olympus Corp, Tokyo, Japan; magnification ×200) and analyzed using Image J software (NIH, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…no. C0078S; Beyotime Institute of Biotechnology), according to the manufacturer's protocol ( 29 ). Positive cells were observed under an Olympus IX71 fluorescent microscope (Olympus Corp, Tokyo, Japan; magnification ×200) and analyzed using Image J software (NIH, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…17 On the other hand, CCL20 contributes to liver fibrosis 19,20 and angiogenesis in malignant tumors. [21][22][23] Thus, CCL20 appears to be involved in autoimmunity/inflammation, vasculopathy and tissue fibrosis, which are the 3 cardinal pathological features of SSc. 2,3,24 Based on these backgrounds, we examined if CCL20 is involved in the development of SSc-associated symptoms and complications.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, data showed that CEPP55 facilitates the EMT process in renal cells and participates in the AKT pathway [42,43]. DEPDC1 has been identified in various cancers, including HCC, breast cancer, and prostate cancer, among others and is positively involved with multiple tumorous biological processes, including proliferation, invasion, and angiogenesis by activating different signaling pathways, such as CCL20/CCR6, E2F et al [44][45][46]. According to previous reports, CLSPN is overexpressed in renal cell carcinoma (RCC) as assessed by immunohistochemistry in 95 RCC cases.…”
Section: Discussionmentioning
confidence: 99%